Microsoft Kinect Sensor Used to Capture Data for Robotics Applications: A Recent Study - Ionel Staretu; Catalin Moldovan (Innovations in Science and Technology Vol. 5, 2022)
The process of capturing digital images has greatly evolved since the initial appearance of photography in general. In recent years, this evolution has been greatly accelerated by the development of high resolution and specialized digital capture sensors which, in turn, has opened the door for research to develop new products and algorithms allowing imaging to be used as input for controlling different other devices or robots. Still, for there to be a real mapping between a digital image and physical word a lot of research has been done in the field of algorithms and sensors, which have lately resulted in the emergence of affordable and specialized devices on the market like Microsoft Kinect or Motion Leap. Initially, the Microsoft Kinect device was exclusively used for the gaming industry, but later captured the attention of the research community, who quickly noticed that the sensor could be used as a very affordable alternative in the three-dimensional mapping process of space. Soon, an SDK was developed by PrimeSense (OpenNI), which allowed the sensor to be used for any other purpose, not just in the field of games. One of these opportunities is the use of the sensor in the field of image analysis for which a product to capture the movement of a human was developed and is presented in this paper along with a proposal to use the capture mechanism to command and control an industrial robotic arm. The presented issues can be used with minimal adaptations and for more advanced Kinect sensor variations that are already underway or will be carried out in the future for similar applications.